Silencing of miR-182 is associated with modulation of tumorigenesis through apoptosis induction in an experimental model of colorectal cancer - Perilli, Lisa (BMC Cancer, 2019)
BACKGROUND: miR-182-5p (miR-182) is an oncogenic microRNA (miRNA) found in different tumor types and one of the most up-regulated miRNA in colorectal cancer (CRC). Although this microRNA is expressed in the early steps of tumor development, its role in driving tumorigenesis is unclear. METHODS: The effects of miR-182 silencing on transcriptomic profile were investigated using two CRC cell lines characterized by different in vivo biological behavior, the MICOL-14(h-tert) cell line (dormant upon transfer into immunodeficient hosts) and its tumorigenic variant, MICOL-14(tum). Apoptosis was studied by annexin/PI staining and cleaved Caspase-3/PARP analysis. The effect of miR-182 silencing on the tumorigenic potential was addressed in a xenogeneic model of MICOL-14(tum) transplant. RESULTS: Endogenous miR-182 expression was higher in MICOL-14(tum) than in MICOL-14(h-tert) cells. Interestingly, miR-182 silencing had a strong impact on gene expression profile, and the positive regulation of apoptotic process was one of the most affected pathways. Accordingly, annexin/PI staining and caspase-3/PARP activation demonstrated that miR-182 treatment significantly increased apoptosis, with a prominent effect in MICOL-14(tum) cells. Moreover, a significant modulation of the cell cycle profile was exerted by anti-miR-182 treatment only in MICOL-14(tum) cells, where a significant increase in the fraction of cells in G0/G1 phases was observed. Accordingly, a significant growth reduction and a less aggressive histological aspect were observed in tumor masses generated by in vivo transfer of anti-miR-182-treated MICOL-14(tum) cells into immunodeficient hosts. CONCLUSIONS: Altogether, these data indicate that increased miR-182 expression may promote cell proliferation, suppress the apoptotic pathway and ultimately confer aggressive traits on CRC cells. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-019-5982-9) contains supplementary material, which is available to authorized users.